Designing Effective AAC Displays for Individuals with Developmental or Acquired Disabilities: State of the Science and Future Research Directions - Light, Janice (Augment Altern Commun, 2019)
This paper reviews research on the impact of AAC display variables on visual attention and performance of children with developmental disabilities and adults with acquired conditions, and considers implications for designing effective visual scene displays (VSDs) or grids. When using VSDs with children with developmental disabilities or adults with acquired conditions, research supports the use of personalized photo VSDs that include familiar people engaged in meaningful activities, with navigation bars with thumbnail VSDs, located adjacent to the main VSD. Adults with acquired conditions seem to benefit from the inclusion of text boxes adjacent to the scene. Emerging evidence supports the use of motion to capture visual attention to VSDs (video VSDs) or to specific elements in VSDs. When using grid displays with children with developmental disabilities, research supports the use of spatial cues and clustering based on internal symbol color to facilitate visual searching and selection. Background color does not seem to facilitate searching for symbols on smaller displays and may actually distract children from processing the meaningful components of symbols. Preliminary research suggests that the organization of onscreen keyboards and the number, types, and pairings of symbols in grids may impact performance of adults with acquired conditions. Directions for future research are discussed.